PERCEPTIONS AND THEIR CORRELATION WITH ENROLLMENT IN THE INDONESIAN NATIONAL HEALTH INSURANCE SCHEME - Ainy, Asmaripa; Idris, Haerawati; Inaku, Hartati; Tembo, Tannia (Universitas Airlangga, 2024)
Background: Health insurance serves as a key mechanism in facilitating wider and more equitable availability of healthcare services, ensuring that every individual can access the services they need. Aims: This research aims to examine the correlation between community perceptions and enrollment in the National Health Insurance (JKN) in the Musi Rawas Utara District, Indonesia. Methods: This research applied a cross-sectional study by collecting data from 384 respondents. Logistic regression analysis was used to assess the correlation between perceptions and JKN enrollment. Results: The results showed that 68.49% of respondents were not enrolled in the JKN. Factors associated with JKN enrollment include perceptions regarding JKN, income, and the history of illness. People with favorable perceptions have a 1.90 times higher chance to join the JKN membership. People with income ≥ provincial minimum wage (UMR) have an opportunity of 0.50 times higher than people with income < UMR to join the JKN membership. The history of illness is likely to enhance JKN enrollment by 7.86 times. Conclusion: In the Musi Rawas Utara District, the rate of enrollment in the JKN program remains low. Strategic policy reforms, accompanied by targeted advocacy and health education promotion, have the potential to significantly increase JKN enrollment and contribute to the realization and sustainability of universal health coverage (UHC) goals. Keywords: Perception, Enrollment, National Health Insurance